2018
DOI: 10.1515/cclm-2018-0379
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation and cancer biomarker discovery: a promising and thorny journey

Abstract: Glycosylation is among the most important post-translational modifications for proteins and is of intrinsic complex character compared with DNAs and naked proteins. Indeed, over 50%–70% of proteins in circulation are glycosylated, and the “sweet attachments” have versatile structural and functional implications. Both the configuration and composition of the attached glycans affect the biological activities of consensus proteins significantly. Glycosylation is generated by complex biosynthetic pathways comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 148 publications
1
87
0
Order By: Relevance
“…The transcripts identified as differentially expressed were those with adjusted p < 0.1 and a difference in fold change > 1. 5 Quantitative Real-Time PCR mRNA was isolated from cells at 60% confluence using the mRNA Capture kit (Roche, Basel, Switzerland) according to the manufacturer's guidelines. cDNA was synthesized with Reverse Transcription System kit (Promega, San Luis Obispo, CA).…”
Section: Microarray Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The transcripts identified as differentially expressed were those with adjusted p < 0.1 and a difference in fold change > 1. 5 Quantitative Real-Time PCR mRNA was isolated from cells at 60% confluence using the mRNA Capture kit (Roche, Basel, Switzerland) according to the manufacturer's guidelines. cDNA was synthesized with Reverse Transcription System kit (Promega, San Luis Obispo, CA).…”
Section: Microarray Analysismentioning
confidence: 99%
“…Glycosylation is one of the most common and complex posttranslational modifications of proteins, and glycans also occur conjugated to lipids (2). Changes in glycosylation are involved in the regulation of many cancer-related processes such as signaling, cell adhesion, tumor proliferation, invasion, metastasis, and angiogenesis (2)(3)(4)(5). Importantly, cancer-associated glycans also provide a set of diagnostic biomarkers and potential targets for therapeutic strategies (2,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant glycosylation has been recognized as a hallmark of cancer. Glycosylation is often involved in the folding, polymerization, maturation and transport of protein peptide chains, which plays an important role in the regulation of cellular functions 3 , 4 . Fucosylation is one of the most common glycosylation modification and many studies revealed that increased fucosylation contributed to many malignant transformation events, such as invasion, metastasis, angiogenesis and immune evasion 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) defines the disease without or having less expression of the well-known breast cancer markers like ER, PR, and HER/neu [18], therefore, requiring different treatment approaches. Glycotherapy is one of the potential strategies to target aberrant glycosylation that promotes abnormal cellular activities and carcinogenesis [19]. The aspragine-linked (N-linked) glycoprotein was found to have roles in the progression of breast cancer, such as angiogenesis [20].…”
Section: Introductionmentioning
confidence: 99%